Design and analysis of a new solar hydrogen plant for power, methane, ammonia and urea generation - Yuksel, Yunus Emre; Ozturk, Murat; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In this paper, a solar power-based combined plant for power, hydrogen, methane, ammonia and urea production is proposed. A parabolic trough collector is utilized for the system prime mover. Moreover, steam Rankine cycle, organic Rankine cycle, hydrogen production and compression subsystem, ammonia, methane and urea production units, single-effect absorption cooling unit, and freshwater production plant are integrated together to develop the present system for better system performance and costeffectiveness and reduced environmental impact. In order to analyze and evaluate the proposed multigeneration plant, thermodynamic, parametric and economic studies are performed. According to the assessment results, it is found that energetic and exergetic efficiencies of the present multigeneration plant are 66.12% and 61.56%, respectively. The comparisons of the subsystem and overall plant efficiencies show that the highest energetic and energetic efficiencies belong to freshwater production plant by 79.24% and 75.62%, respectively. In addition, the present parametric analysis indicates that an increase in the reference temperature, solar radiation intensity and working pressure of the solar process has a positive effect on the plant's performance. The cost analysis reveals that as the solar radiation intensity and the working pressure of the solar process increase, the hydrogen generation cost decreases. Furthermore, the hydrogen generation cost is achieved to be 1.94 $/kgH2 at 650 W/m2 of the solar radiation intensity, with other parameters
Keywords: Solar energy; Multigeneration system; Integrated system; Thermodynamic analysis; Hydrogen; Ammonia; Methane; Urea; INTEGRATED-SYSTEM; PERFORMANCE ANALYSIS; EXERGY ANALYSIS; CYCLE; OPTIMIZATION; Chemistry; Electrochemistry; Energy & Fuels